2017
DOI: 10.1016/j.ynstr.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics reveals distinct neurochemical profiles associated with stress resilience

Abstract: Acute social defeat represents a naturalistic form of conditioned fear and is an excellent model in which to investigate the biological basis of stress resilience. While there is growing interest in identifying biomarkers of stress resilience, until recently, it has not been feasible to associate levels of large numbers of neurochemicals and metabolites to stress-related phenotypes. The objective of the present study was to use an untargeted metabolomics approach to identify known and unknown neurochemicals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 86 publications
1
30
0
Order By: Relevance
“…All animals were tested for a CD response 24 hours later. During acute social defeat stress, subjects were consecutively placed in the home cages of three separate resident aggressors for 5-min each with 5-min inter-trial intervals, as described previously 27,28 . No defeat control animals were treated identically except that the aggressors were removed from their cages to control for olfactory and environmental exposure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All animals were tested for a CD response 24 hours later. During acute social defeat stress, subjects were consecutively placed in the home cages of three separate resident aggressors for 5-min each with 5-min inter-trial intervals, as described previously 27,28 . No defeat control animals were treated identically except that the aggressors were removed from their cages to control for olfactory and environmental exposure.…”
Section: Resultsmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Dominant-subordinate encounters. To allow the establishment of dominance relationships, subjects were individually housed for 1 week following stereotaxic surgery and were then weight-matched into resident-intruder dyads and paired in daily social encounters for 14 days as described previously 27,28 . Briefly, subjects were randomly assigned as a resident or intruder, and all social encounters occurred in the resident's home cage.…”
Section: Scientific Reports |mentioning
confidence: 99%
See 1 more Smart Citation
“…In another animal model, optogenetic stimulation of the vmPFC-DRN circuit during an acute forced swim stressor promotes proactive behavioral responses (Warden et al, 2012), which have been argued to index stress resilience (e.g., Wood et al, 2010). In our laboratory, we have shown that male Syrian hamsters who maintain social dominance for 2 weeks exhibit fewer negative behavioral (Morrison et al, 2014), neuroendocrine (Dulka et al, 2018b), and neurochemical (Dulka et al, 2017) consequences of social defeat stress compared to subordinates or controls. Importantly, such status-dependent changes in behavior require recruitment of vmPFC neurons (Morrison et al, 2013) and correspond with reduced activity of the DRN during social and non-social acute stress (Cooper et al, 2017).…”
Section: Introductionmentioning
confidence: 67%
“…Various forms of acute social stress have been described [22,63,83], but a standardized ASDS protocol resulting in distributions of resilience and susceptibility similar to CSDS has not previously been validated to the best of our knowledge. Experimental mice were placed into the cages of three aggressive CD1 mice for 2 min each sequentially, without rest periods.…”
Section: Animalsmentioning
confidence: 99%